An unusual association between hemophagocytic lymphohistiocytosis, mixed connective tissue disease, and autoimmune hemolytic anemia: A case report. Issue 28 (July 2017) - Kelkar, Amar H.; Shah, Anushi A.; Yong, Sherri L.; Ahmed, Zohair
Abstract: Rationale: In the adult patient, hemophagocytic lymphohistiocytosis (HLH) is uncommon and frequently difficult to diagnose due to its nonspecific presentation and numerous complications. Patient concerns: Herein, we present the case of a 25-year-old female who initially presented for evaluation of persistent fevers and fatigue. She was found to have splenomegaly, generalized lymphadenopathy, pancytopenia, and acute hepatic failure. Diagnoses, Interventions, and Outcomes: Her course was further complicated by the development of nephrotic syndrome and autoimmune hemolytic anemia (AIHA). Antinuclear antibody and ribonucleoprotein were positive, with concurrent physical examination findings, indicating underlying mixed connective tissue disease (MCTD). Ferritin was greater than 40, 000 ng/dL. Viral studies, including hepatitis A, B, and C, cytomegalovirus, and Epstein–Barr virus were negative. On the basis of her clinical presentation, a diagnosis of HLH secondary to MCTD was made. This was later confirmed on liver biopsy. She was started on high-dose prednisone and her symptoms completely resolved. She was then transitioned to azathioprine, hydroxychloroquine, prophylactic antibiotics, and a prednisone taper for long-term management. Lessons: This case is notable for the association of both AIHA and MCTD with HLH, providing support for a possible relationship between these 3 conditions.